Are postnatal traumatic events an underestimated cause of porencephalic lesions in dogs and cats? - Davini, Tommaso; Mattei, Chiara; La Rosa, Claudia; Remelli, Carlotta; Specchi, Swan; Lionello, Elena; Dell’Era, Elena; Bernardini, Marco (Frontiers in Veterinary Science, 2023)
Porencephaly is defined as a fluid-filled cavity of variable size in the brain cortex. It is regarded as a congenital condition and is typically considered a developmental or an encephaloclastic defect. Our hypothesis is that postnatal traumatic events in the first few months of life may represent a cause of canine and feline porencephaly that is more common than generally suspected. The aims of this study were to retrospectively investigate porencephaly in a large population of dogs and cats, detect MRI features that might be useful to differentiate postnatal acquired traumatic forms from congenital/perinatal porencephaly, and define the prevalence of seizure activity in porencephalic patients.This is a double-center, descriptive, retrospective case series. Databases were searched for cases within a 17-year time span that involve dogs and cats with an MRI-based diagnosis of cerebral cavitary lesions. Animals were included if a complete signalment and an exhaustive MRI of the brain were available. Besides the porencephalic lesions, MRIs of the head were reviewed to detect concomitant musculoskeletal abnormalities.Results: Thirty-two cases involving nine cats and twenty-three dogs were selected. Of all the cases, 21.9% were aged six years or older at the time of diagnosis. All patients in which the neuroanatomical localization was available showed clinical signs of a prosencephalic disorder. Epileptic seizures were observed in 71.8% of cases. A single porencephalic cavity was found in 78.1% of cases. The most affected cerebral lobe was the parietal lobe (n=20). The defects involved both the grey and white matter in 78.1% of cases. Twenty cases showed concomitant musculoskeletal abnormalities overlying the porencephalic cavities. Fourteen of twenty cases showed evidence of fractures, of which thirteen showed depression of the calvarium and twelve masticatory muscle abnormalities. Of these, seven of fourteen had a history consistent with a head trauma in the first period of life.The recognition of skull fractures and muscular abnormalities closely associated with the porencephalic cavity may support a diagnosis of a postnatal traumatic origin of porencephaly.Therefore, this study highlights the importance of evaluating musculoskeletal structures in the MRIs of the heads of porencephalic cases.